Westdeutscher Künstlerbund 1989 : 23. Ausstellung. (Hagen : Karl Ernst Osthaus-Museum, 1989)
Abrell, Hermann ; Armborst-Wimmershoff, Annette ; Binder, Rolf ; Böhm, Hartmut ; Bonato, Victor ; Bormann, Peter ; Brandmeier, Monika ; Cone Weeks, Stephen ; Deitmar, Toni ; Dohr, Günter ; Drebber, Magdalena ; Driller, Brigitte ; Dümling, Brigitte ; EsRichter, Hermann, Fischer, Jochen ; Friege, Heinz ; Fromm, Oliver ; Grigat, Ulla ; Grochowizk, Thomas ; Haarlammert, Ulrich ; Hagenberg, Helfried ; Hegmann, Susanne ; etc.
Westdeutscher Künstlerbund 1989 - 23. Ausstellung, Karl Ernst Osthaus-Museum, Hagen, 4. Juni bis 16. Juli 1989
boek